Pengaruh Fraud Hexagon terhadap Perilaku Kecurangan Akademik Mahasiswa Akuntansi di Kota Kupang - Minshy L. Tameno; Moni W. Muskanan; Yohana F. Angi (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
This research aims to determine the influence of the Fraud Hexagon theory on the academic fraud behavior of accounting students in Kupang City. This research employs a quantitative approach using the IBM SPSS 25 analysis tool. The research objects encompass four universities in Kupang City, namely Universitas Nusa Cendana, Universitas Katolik Widya Mandira, Universitas Kristen Artha Wacana, and Universitas Muhammadiyah Kupang. The results of this research indicate that the elements within the Fraud Hexagon theory, namely rationalization, arrogance, and collusion, have an influence on the academic fraud behavior of accounting students in Kupang City. The elements of pressure, opportunity, and capability do not have an influence on the academic fraud behavior of accounting students in Kupang City. Simultaneously, pressure, opportunity, rationalization, capability, arrogance, and collusion influence the academic fraud behavior of accounting students in Kupang City.